EKSISTENSI HINGGA EKSITASI OLEH CIVIL SOCIETY DALAM MENCIPTAKAN GOOD GOVERNANCE DI INDONESIA (ANALISIS PENDEKATAN BEHAVIORAL PADA WACANA KPK VERSUS POLRI) - Rudi Salam Sinaga (PERSPEKTIF, 2014)
Good Governance emphasizes attention to realize that there are some essential elements in good governance namely Accuntability, Participation, predictability, and Transparency. Another important thing is not to lose should be fulfilled in the realization of good governance is to honor law enforcement presence that is jointly supervised by public. This study aims to examine the reality of the phenomenon of conflict between the discourse of anti-corruption commission (KPK) with the Indonesian National Police (INP) related discourse â€œgecko versus crocodileâ€. This study will look at how the existence of Civil Society in conducting excitations to the creation of good governance in Indonesia, Study on chaotic discourse Versus the Police Commission. This research was descriptive qualitative method of data collection techniques using analytical approach to literature and media discourse. The results of this study indicate the presence of public power that collectively perform excitation in to the realization supermacy of law.